口蓋裂を伴った上顎体の1 例 - 谷口, 佳孝; 西尾, 順太郎; 並川, 麻理; 小原, 浩; 平野, 吉子 (日本口腔外科学会雑誌, 2009)
Epignathus is an extremely rare congenital teratoma that arises from the upper jaw, palate, or pharynx.It usually protrudes through the mouth, leading to obstruction of the upper airway and death soon after birth. We report a case of epignathus combined with cleft palate. The patient weighed 2040 g in the 34th week 2nd day of gestation. The stalk of the tumor developed from the oropharynx through the cleft palate. Surgical removal of the tumor was performed when the patient was 60 days old. Histopathological examination revealed that the tumor was a mature teratoma containing three germ layers, including nerve tissue, squamous epithelium, cartilage, mucous glands, and respiratory epithelium. Cleft palate repair is planned.